Älter, hörbeeinträchtigt und…. erwerbstätig! - Andreas Weber; Ulrike Weber (Journal for Labour Market Research, 2015)
– Until recently in Germany, there has been a lack of meaningful data or statistics related to that segment of the population that is disabled yet still part of the active workforce, including older working people. Since 2009, Project GINKO has been tackling this gap in research for this section of employed, hearing-impaired people (through communication and organization, GINKO specifically studies the effect legislation has had on the professional integration of the hard-of-hearing, those who have lost their hearing and deaf people). One of the study's objectives is to analyze the conditions involved in professionally integrating the hearing-impaired into the workforce, with particular reference to the issue of legal mobilization of SGB IX, including its specific implementation during the average work day by structuring the workplace to meet the needs of the disabled as defined under 81(4) SGB IX, e.g. by providing technical assistance. Nationwide, every disabled person who was part of the GINKO study was provided with a standardized survey – which was also available online as sign language videos – asking them about the contents of the current legislation and their workplace situation. Overall, n?=?3,189 severely disabled working persons responded to the GINKO survey, of whom n?=?661 (20.7?%) were between 50 and 65 years were old. The percentage of female workers in this age group was 48.7?%. The results of the GINKO project showed that the measures provided by 81 para 4, SGB IX for configuring disability-friendly workplaces for elderly hearing-impaired employees have been rather minimal. Thus, data analysis for older, professionally active participants (n?=?661) regarding how their workplaces are configured showed that only 29.6?% of this group judged their workplace overall as meeting the needs of the hearing impaired. In particular, technical aids such as FM systems or additional microphones are not available to many of the employed participants, although they could use them. Also important for people with hearing impairment is noise reduction in the workplace, such as sound insulation, which has only been taken into account for about a third of respondents. Thus, GINKO project analyses show that further efforts are needed to actually implement existing legal options.
Keywords: 330; Hörbehinderte; Gehörlose; berufliche Integration; Erwerbsbeteiligung; behindertengerechte Arbeitsplätze; technische Hilfe; Sozialgesetzbuch IX; Behindertenrecht; ältere Arbeitnehmer; Arbeitsbedingungen